The socioeconomic impact of multiple sclerosis in France: Results from the PETALS study. Issue 2 (April 2022) - Bouleau, A; Dulong, C; Schwerer, CA; Delgrange, R; Bouaou, K; Brochu, T; Zinai, S; Švecová, K; Sá, MJ; Petropoulos, A; Aly, S; Labauge, P
Background: Multiple sclerosis (MS) places a considerable financial burden on the society. However, data quantifying the contemporary cost burden in France are lacking. Objective: This cost-of-illness study aimed to estimate the direct and indirect costs associated with MS in France. Methods: Between October 2020-November 2020, 208 French adults with a confirmed diagnosis of MS were recruited via MSCopilot ® (a new MS self-assessment digital solution) and several MS patient networks. Indirect costs were estimated using a combination of top-down and bottom-up approaches. Direct costs were retrieved from Assurance Maladie (i.e. national system of health insurance) publications. Out-of-pocket expenses (OOPEs) incurred by MS patients were also reported. All costs were expressed in €2020. Data from the survey were extrapolated to the overall French MS population. Results: MS exerted an annual cost burden of €2.7 billion on the French society (indirect costs: €1.3 billion; direct costs: €1.4 billion). Mean annual costs were €27, 164.7 per-patient, with indirect and direct costs accounting for 48.1% and 51.9% of the total annual costs, respectively. OOPEs contributed over €90 million to the total annual costs. Conclusions: MS imposes a substantial cost burden on the French society, with approximately half of the total annual costs driven by indirect costs.